Effect of different expanded aggregates on the properties of lightweight concrete. Issue 2 (3rd April 2018) - Abd Elrahman, Mohamed; Chung, Sang-Yeop; Stephan, Dietmar
Abstract : Lightweight aggregate concrete is a material which has much lower density than normal concrete and many advantages, including advanced insulation performance due to its highly porous or cellular characteristics. Several types of lightweight aggregates have been used to produce lightweight aggregate concrete, and the characteristics of such lightweight aggregates strongly affect the material properties. In this study, three different expanded materials – expanded glass (Liaver), expanded clay (Liapor) and foam glass (Ecoglas) – were utilised as lightweight aggregates, and their effects on the properties of lightweight concrete were investigated. These expanded lightweight aggregates are light and have lower thermal conductivity as well as water absorption than those of normal aggregates. Microstructural characteristics of the specimens with different types of aggregate were examined using X-ray micro-computed tomography. The thermal (thermal conductivity) and mechanical (compressive strength) properties of the lightweight concrete specimens were evaluated experimentally and numerically. The relationship between the physical properties and characteristics was analysed to demonstrate the effect of each expanded aggregate on lightweight aggregate concrete.